INTRAVAGINAL BRACHYTHERAPY SUPPORTED BY LOCAL ANAESTHESIA IN THE TREATMENT OF ENDOMETRIAL CANCER – SINGLE INSTITUTIONAL EXPERIENCE - Klisarovska V; Smichkoska S; Stojkovski I; Djundeva J; Bojoski P; Hristovska E (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University Skopje, R.N.Macedonia, 2020)
Intravaginal brachytherapy in endometrial cancer is an inevitable part of the treatment. In the early stages of the disease, it signifcantly reduces the risk of local recurrence in the vaginal cuff with low rates of late toxicity. In the advanced stages, it provides palliative control usually with a hemostyptic effect. Brachytherapy may be the only postoperative treatment – monotherapy, or as a boost following the external beam radiotherapy, depending on many prognostic factors. Placing the vaginal applicator deep into the vagina is certainly an uncomfortable feeling, combined with pain, anxiety and discomfort. Local anaesthesia helps in reducing the painful sensations, gives adequate relaxation, but more importantly provides a quality insight into the condition of the vagina, and thus a successful application. Through our experience with the local vaginal anaesthesia with lidocaine 2% gel, we want to emphasize that intravaginal brachytherapy, supported by local anaesthesia, regardless of the degree of pain relief is directly related to successful treatment.
Keywords: anaesthesia; analgesia; endometrial cancer; intravaginal brachytherapy